Reconstituting typeset Marriage Registers using simple software tools - Brailsford, David F. (Springer-Verlag, 2012)
In a world of fully integrated software applications, which can seem daunting to develop and to maintain, it is sometimes useful to recall that a system of loosely-linked software components can provide surprisingly powerful and flexible methods for software development.